2020
DOI: 10.1101/2020.11.17.386615
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Long-term stability of avalanche scaling and integrative network organization in prefrontal and premotor cortex

Abstract: Ongoing neuronal activity in the brain establishes functional networks that reflect normal and pathological brain function. Most estimates of these functional networks suffer from low spatiotemporal resolution and indirect measures of neuronal population activity, limiting the accuracy and reliability in their reconstruction over time. Here, we studied the stability of neuronal avalanche dynamics and corresponding reconstructed functional networks in the adult brain. Using chronically implanted high-density mi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 72 publications
(182 reference statements)
0
6
0
Order By: Relevance
“…These original scaling operations for avalanches involved >10 h of continuous recordings in vitro, which is difficult to achieve under standard experimental conditions. Recently, Miller et al [71,77] extended this scaling analysis of LFP-based avalanches. They identified a scaling exponent of two for an avalanche waveform and a mean size vs. duration relationship in line with predictions for a critical branching process.…”
Section: Temporal and Spatial Scaling Links Size Distribution Slope −3/2 To A Critical Branching Parameter For Neuronal Avalanchesmentioning
confidence: 99%
See 1 more Smart Citation
“…These original scaling operations for avalanches involved >10 h of continuous recordings in vitro, which is difficult to achieve under standard experimental conditions. Recently, Miller et al [71,77] extended this scaling analysis of LFP-based avalanches. They identified a scaling exponent of two for an avalanche waveform and a mean size vs. duration relationship in line with predictions for a critical branching process.…”
Section: Temporal and Spatial Scaling Links Size Distribution Slope −3/2 To A Critical Branching Parameter For Neuronal Avalanchesmentioning
confidence: 99%
“…Since network connectivity was found to support avalanche dynamics in dissociated cultures, it could be considered a control parameter as well [119]. On the other hand, measurements in organotypic cortex cultures and in nonhuman primates in vivo demonstrate that avalanches establish integrative network architectures that are robust to certain plastic changes [77,120,121]. Of note, in vivo studies have shown avalanches to be exquisitely sensitive to the sleep/wakefulness transition [122][123][124][125][126], suggesting sleep [127,128] and sleep-arousal transitions [129] as a behavioral state control parameter.…”
Section: Control Parameters Identified In the Regulation Of Neuronal Avalanchesmentioning
confidence: 99%
“…But most importantly, reoccurring sequences of spike patterns with a particular composition of participating units were indeed observed in experiments [64][65][66][67][68][69][70][71], indicating a robust formation of assemblies during signal processing.…”
Section: Analytical Avalanche Size Distributions In Small or Structur...mentioning
confidence: 82%
“…It has been Brain Sci. 2021, 11, 1125 2 of 16 reported that primary motor cortex (M1) neuronal signals can be used to predict the direction and velocity of arm movements [5,6], based on which a brain-machine interface was developed to help those who suffer from paralysis. However, such systems still present a series of issues regarding the flexibility and robustness of control.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have investigated the innervation relationships between neuronal activity patterns from various brain structures and different behaviors [ 2 , 3 , 4 ]. It has been reported that primary motor cortex (M1) neuronal signals can be used to predict the direction and velocity of arm movements [ 5 , 6 ], based on which a brain–machine interface was developed to help those who suffer from paralysis. However, such systems still present a series of issues regarding the flexibility and robustness of control.…”
Section: Introductionmentioning
confidence: 99%